Evaluation of Therapy in Preeclampsia Patients in Several Public and Private Hospitals - Juwita, Dina Ratna; Raykhan, Akhmad Amar; Nimas Arumsari; Putri, Irsalina Nurul; Ambarwati, Dewi (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To determine the rationality and effectiveness of therapy in preeclampsia patients at the Inpatient Installation of several public and private hospital in Banyumas area from January-December 2021. Methods: This study is retrospective, employing purposive sampling for data collection. The data were extracted from the medical records of patients diagnosed with pre-eclampsia at the Inpatient Installation. The sample consisted of 212 patients with a confirmed diagnosis of pre-eclampsia. Results: From this study, it was found that antihypertensive medications given were methyldopa (52.8%), nifedipine (45.2%), and amlodipine (2%). It was found that the results of the five appropriate analyses were the suitable indication, right patient, proper medication, right dose, and correct route (100%). The antihypertensive medications used were effective in reducing the blood pressure of preeclampsia patients (100%), with an average decrease in systolic pressure by 37 mmHg, an average decrease in diastolic pressure by 22 mmHg, and an average decrease in MAP by 28 mmHg. Conclusion: Antihypertensives given to preeclampsia patients in several public and private hospitals in Banyumas were rational and effective in reducing the patient's blood pressure. Keywords: antihypertensives, effectiveness, preeclampsia, rationality.